Human Genetic Engineering: Should Indonesia Regulate It? - Hari Sutra Disemadi (Faculty of Law, Universitas Padjadjaran, 2022)
Human genetic engineering raises pros and cons. Despite the potential to contribute to the health sector, it can cause several problems. While, in theory, it goes against nature and against other conservative beliefs, human genetic engineering gains important support from Transhumanism—a philosophy promoting the scientific evolution of the human race. This study determines the relevancy regulation of human genetic engineering on a global scope and how it affects the prospects of regulating human genetic engineering in Indonesia. The study aims to provide consideration for Indonesia in determining the legality status of human genetic engineering, through analyses of legal constructions surrounding it. The study used a comparative legal research method, using laws and legislations as the focal point to compare the legal frameworks of Indonesia and other countries. It employed secondary data and applied the qualitative method. The study reveals that some countries have already regulated the issue based on the benefits and risks, laying out the boundaries and restrictions on the issue. Indonesia has not established any regulation or showed specific interest in regulating human genetic engineering. The regulation on human genetic engineering is very important because many institutions are now increasingly carrying out human genetic engineering; and many countries oversee it. This importance is based on the theory of legal progressivity, which states that the law exists for human and not the other way around. It implies the necessity of adding progressive moves into the existing legal framework to adapt to the changes and developments in society.DOI: https://doi.org/10.22304/pjih.v9n3.a4